1998
DOI: 10.3109/08977199809017485
|View full text |Cite
|
Sign up to set email alerts
|

A Neu Differentiation Factor (NDF) Domain Essential for Proliferation and Alterations in Morphology of Colonic Epithelial CellsIn Vitro

Abstract: The Neu Differentiation Factors (NDFs, also termed "heregulins") are a family of proteins that were first isolated as ligands for the HER2 (ergB2, or p185neu) receptor protein tyrosine kinase. Here we show that NDF acts to stimulate the proliferation and alter the cellular morphology of colonic epithelial cells in culture. Dramatic NDF-induced changes in cellular morphology were noted in the colonic epithelial cell line, LIM 1215. In addition, the expression of specific cell proteins, such as carcinoembryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…repair of the epithelium itself, especially as the NRG-1␣ isoforms are not up-regulated in the olfactory bulb (Meyer et al,1997;al Moustafa et al, 1999). NRG-1s have been reported to induce morphological changes and proliferation in epithelial cells of different origins (Chausovsky et al, 1998;Whoriskey et al, 1998) In addition, NRG-1␣2 has been found to be present in epidermis during tissue repair (Danilenko et al, 1995;Ram et al, 1995). Changes were also seen in the type 1␤ isoform with regards to the presence or absence of the spacer domain.…”
Section: Mrna Expression Of Nrg-1 Isoforms In the Olfactory System Afmentioning
confidence: 80%
“…repair of the epithelium itself, especially as the NRG-1␣ isoforms are not up-regulated in the olfactory bulb (Meyer et al,1997;al Moustafa et al, 1999). NRG-1s have been reported to induce morphological changes and proliferation in epithelial cells of different origins (Chausovsky et al, 1998;Whoriskey et al, 1998) In addition, NRG-1␣2 has been found to be present in epidermis during tissue repair (Danilenko et al, 1995;Ram et al, 1995). Changes were also seen in the type 1␤ isoform with regards to the presence or absence of the spacer domain.…”
Section: Mrna Expression Of Nrg-1 Isoforms In the Olfactory System Afmentioning
confidence: 80%
“…Such a process may be involved in the development of tumorigenesis [31]. In vitro, Nrg1 acts to stimulate the proliferation and alters the cellular morphology of colonic epithelial cells in culture, with Nrg1b exhibiting more pronounced effects than the alpha isoform [32]. NRG4 and ErbB4 were also found to be mainly expressed in mucosa-associated lymphoid tissue (MALT) and follicular lymphoma, where they function in the proliferation of malignant lymphoma cells in the GI tract [33].…”
Section: Discussionmentioning
confidence: 99%
“…Exchange studies between NRG-1␣ and NRG-1␤ show that particularly the linear C-terminal region determines the binding properties and mitogenic potential of these isoforms (25). Therefore, it has been proposed that NRGs may have a bivalent character and interact with both ErbB-3 and ErbB-2 through separate binding sites (26).…”
mentioning
confidence: 99%